2017
DOI: 10.1098/rspb.2017.2188
|View full text |Cite
|
Sign up to set email alerts
|

The early Cambrian fossil embryoPseudooidesis a direct-developing cnidarian, not an early ecdysozoan

Abstract: Early Cambrian Pseudooides prima has been described from embryonic and post-embryonic stages of development, exhibiting long germ-band development. There has been some debate about the pattern of segmentation, but this interpretation, as among the earliest records of ecdysozoans, has been generally accepted. Here, we show that the ‘germ band’ of P. prima embryos separates along its mid axis during development, with the transverse furrows between the ‘somites’ unfolding into the polar aperture of the ten-sided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…These analyses used a dataset of 93 taxa (20 fossils) and 278 adult and embryological characters. The new matrix builds on previously available datasets [2,11,13,53] through the incorporation of new morphological information and an expanded taxon sample (Figures 6 and S7).…”
Section: Homology Of Body Regions and The Phylogenetic Position Of ''mentioning
confidence: 99%
See 1 more Smart Citation
“…These analyses used a dataset of 93 taxa (20 fossils) and 278 adult and embryological characters. The new matrix builds on previously available datasets [2,11,13,53] through the incorporation of new morphological information and an expanded taxon sample (Figures 6 and S7).…”
Section: Homology Of Body Regions and The Phylogenetic Position Of ''mentioning
confidence: 99%
“…Numbers at the nodes are posterior probabilities, and the scale bar is in units of the expected number of substitutions per site. The dataset is expanded and modified from previous datasets [2,11,13,53] to include ''dinomischids,'' which form a paraphyletic grade on the ctenophore stem. See also Methods S1 and Figure S7 for additional analyses using other optimality criteria.…”
Section: Figure 6 Phylogenetic Analysismentioning
confidence: 99%
“…The Cambrian Period contains only a very low diversity of cnidarians that can be confidently ascribed to major modern groups, particularly at the ordinal level (Landing et al, ; Scrutton, ; Stanley Jr, ). Of what can be confidently ascribed to a modern group, all are medusozoans, which are abundant and well documented even in the lower Cambrian (Dong et al, ; Duan et al, ; Zhao & Bengtson, ). All of the modern Anthozoan orders (Alcyonacea, Helioporacea, Pennatulacea, Actiniaria, Antipatharia, Corallimorpharia, Scleractinia, Zoantharia and Ceriantharia) cannot have their history traced back as far as the Cambrian Period.…”
Section: Comparison To the Fossil Record Of Soft‐bodied Cnidariansmentioning
confidence: 99%
“…Other taxa such as Eolympia pediculata are compellingly anthozoan but are difficult to place more precisely (Han et al, ). There are undoubted crown group cnidarian fossils found in the Cambrian Period (Duan et al, ), and there is no doubt of the antiquity of total group Cnidaria being at least to the Cambrian Period. However, the major radiative burst of anthozoan evolution that generated the modern orders seems to have been a little later, in the earliest Ordovician.…”
Section: Comparison To the Fossil Record Of Soft‐bodied Cnidariansmentioning
confidence: 99%
“…Thanks largely to the results of highly sophisticated studies of olivooid anatomy and development, combined with the application of cladistic methodologies to the problem of olivooid affinities, there now appears to be a consensus that olivooids were crown- or stem-group medusozoan cnidarians (see in particular Han et al, 2013, 2016a, b; Dong et al, 2016; Duan et al, 2017), though with fairly substantial disagreement over the phylogenetic relationships of olivooids to major groups within the subphylum. Thus, whereas Yue and Bengtson (1999), Dong et al (2013, 2016), and Duan et al (2017) argued for a scyphozoan affinity for olivooids, Han et al (2013, 2016a) argued that olivooids were stem-group cubozoans. In addition, Dong et al (2016) and Duan et al (2017) concluded that olivooids were members of a clade of scyphozoans that included conulariids, an extinct group that ranges downward into the terminal Proterozoic ( Paraconularia sp.…”
Section: Introductionmentioning
confidence: 99%